Pengaruh Volume Pembiayaan Bagi Hasil Dan Pembiayaan Murabahah Terhadap Kinerja Keuangan Bank Umum Syariah Periode 2015-2020 - Quatro, Celine; Asnaini, Asnaini; Oktarina, Aminah (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2021)
This study aims to determine the effect of profit-sharing volume and murabahah financing on the performance of Islamic commercial banks for the 2015-2020 period. This research uses ECM (Error Correction Model) analysis with Eviews 8 software. The sample used in this study is 13 Islamic commercial banks that have been registered with the Indonesian Financial Services Authority (OJK). The sampling technique used the purposive sampling method because researchers needed certain criteria, namely Islamic commercial banks that have published financial ratios. The data used in this study are secondary data with documentary data collection techniques and literature studies. The results of this study indicate that the R square value is 0.0362370 indicating that 36% of changes in the ROA variable can be explained by independent variables and 64% are explained by other factors outside the model..